Biopile Sebagai Teknologi Ramah Lingkungan Untuk Remediasi Tanah Tercemar Timbal - Salim, Awwalini Maghfirah; Alricha, Alricha; Kadir, Iin Nindy Karlinda; Pratiwi, Anita; Amaludin, Moh. Baitullah; Marjan, M (Lambung Mangkurat University Press, 2025)
Soil contamination by the heavy metal lead (Pb) poses a significant threat to public health and ecosystems. This study evaluated the effectiveness of the ex-situ biopile method for remediating Pb-contaminated soil at the Kawatuna Landfill, Palu City. Soil samples were collected from the contaminated site and treated in a biopile prototype with controlled aeration and moisture, with the addition of compost as an amendment at 10% (w/w). Laboratory analyses conducted at the Integrated Laboratory of Tadulako University showed a decrease in total Pb concentration from 41.96 mg/kg to 31.83 mg/kg after seven days of treatment. This corresponds to a removal efficiency of 24.13% and an average degradation rate of 1.45 mg/kg·day. These results indicate that the biopile method is capable of reducing Pb concentrations in soil during the initial stage of treatment; however, optimization of treatment duration and operational conditions is required to achieve regulatory soil quality standards. Furthermore, the use of locally sourced compost as a nutrient amendment and the absence of secondary waste generation support the biopile method as an environmentally friendly and cost-effective soil remediation technology.